2019
DOI: 10.1161/circulationaha.119.039596
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Translational Control of Fibrosis in the Human Heart by RNA-Binding Proteins

Abstract: ◼ fibrosis ◼ ribosome profiling ◼ RNAbinding proteins ◼ TGF-beta1 Sources of Funding, see page 949 BACKGROUND: Fibrosis is a common pathology in many cardiac disorders and is driven by the activation of resident fibroblasts. The global posttranscriptional mechanisms underlying fibroblast-to-myofibroblast conversion in the heart have not been explored. METHODS: Genome-wide changes of RNA transcription and translation during human cardiac fibroblast activation were monitored with RNA sequencing and ribosome prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 49 publications
(62 reference statements)
3
102
0
Order By: Relevance
“…This locus furthermore co-localized with a highly replicated QTL for cardiac mass (Inomata et al, 2005;Siegel et al, 2003), for which a loss-of-function insertion in endonuclease G (Endog) was previously identified as a driver of cardiomyocyte hypertrophy and increased left-ventricular weight (McDermott-Roe et al, 2011). Among all genes associated with this master regulatory teQTL, we found strong enrichment for extracellular matrix (ECM) proteins (11 out of 25; GO:0031012; p adj = 3.32 × 10 -10 ) (Figure 2A and 2B), consistent with recent observations of strong translational control of fibrotic processes in human hearts (Chothani et al, 2019;Heesch et al, 2019).…”
Section: Distant Teqtl "Hotspots" Are Master Regulators Of Cardiac Trsupporting
confidence: 89%
“…This locus furthermore co-localized with a highly replicated QTL for cardiac mass (Inomata et al, 2005;Siegel et al, 2003), for which a loss-of-function insertion in endonuclease G (Endog) was previously identified as a driver of cardiomyocyte hypertrophy and increased left-ventricular weight (McDermott-Roe et al, 2011). Among all genes associated with this master regulatory teQTL, we found strong enrichment for extracellular matrix (ECM) proteins (11 out of 25; GO:0031012; p adj = 3.32 × 10 -10 ) (Figure 2A and 2B), consistent with recent observations of strong translational control of fibrotic processes in human hearts (Chothani et al, 2019;Heesch et al, 2019).…”
Section: Distant Teqtl "Hotspots" Are Master Regulators Of Cardiac Trsupporting
confidence: 89%
“…However, this approach does not take into account the variance, low expression of RPFs or mRNA counts, or batch effects, severely compromising the accuracy of detection. Several other approaches to detect DTEGs by modeling changes in TE have Chothani et al (Chothani et al, 2019), four pair-wise comparisons)…”
Section: Figurementioning
confidence: 99%
“…However, in the presence of a batch effect or based on the data from Xiao et al (2016), TE is superior. To further verify that this effect is not confined to simulated data, we analyzed RNAseq and Ribo-seq data derived from our recent study on cardiac fibrosis (Chothani et al, 2019). This experiment contained cardiac fibroblasts from four different individuals, and, as a result, has a pronounced patient-related batch effect accounting for roughly 25% of the variance within the data.…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Other studies also showed that circulating miR-103a-3p leads to angiotensin II-induced renal inflammation and fibrosis through an SNRK/NF-κB/p65 regulatory axis. LncRNAAK081284, miR-489, and miR-455 influence cardiac fibrosis [ 39 , 40 , 41 ]. However, the roles of noncoding RNAs in arachnoid fibrosis and hydrocephalus remain unclear.…”
Section: Discussionmentioning
confidence: 99%